Estrategia para promocionar el patrimonio cultural desde la relación turista - anfitrión en Hostales del destino Santa Clara. - Rodríguez Mendez, Ariel (Universidad Central "Marta Abreu" de Las Villas, 2013)
El fenómeno del turismo es capaz de asociar y reunir a numerosas grupos de individuos. Socializar e intercambiar conocimientos, tradiciones y cultura se convierten en acciones principales que suceden entre los turistas y los anfitriones. La presente investigación está basada en caracterizar la relación turista-anfitrión en los hostales de la ciudad de Santa Clara. Por lo que el objetivo general de esta investigación es Diseñar la Estrategia para promocionar el patrimonio cultural de la ciudad de Santa Clara a partir de la relación turista-anfitrión que se da en los Hostales. Donde se estudian conceptos como turismo, relación turista-anfitrión, hostales, arrendamiento, entre otros. Esta investigación se rige por los presupuestos materialista-dialécticos, utilizando esencialmente la metodología cualitativa. Con el fin de realizar una satisfactoria investigación se utilizan métodos y técnicas como la observación participante, el análisis de documentos y entrevistas semiestandarizadas, que permiten la recopilación de información a partir de desarrollar un tratamiento metodológico a las variables para determinar esta relación y la utilización del Procedimiento de diagnóstico de recursos turísticos patrimoniales tangibles e intangibles para desarrollar el inventario de recursos que pueden ser promocionados por parte de los hosteleros.

The phenomenon of the tourism is able to associate and to gather to numerous groups of individuals. To socialize and to exchange knowledge, traditions and culture becomes main actions that happen between the tourists and the hosts. The present investigation is based on characterizing the relationship tourist-host in the inns of Santa Clara's city. For what the general objective of this investigation is to Design the Strategy to promote the cultural patrimony of Santa Clara's city starting from the relationship tourist-host that is given in the Inns. Where concepts like tourism are studied, relationship tourist-host, inns, lease, among others. This investigation is governed by the materialistic-dialectical budgets, using the qualitative methodology essentially. With the purpose of carrying out a satisfactory investigation methods they are used and technical as the participant observation, the analysis of documents and interviews semiestandarizadas that allow the summary of information starting from developing a methodological treatment to the variables to determine this relationship and the use of the Procedure of diagnosis of tangible and intangible patrimonial tourist resources to develop the inventory of resources that you/they can be promoted on the part of the innkeepers The relationship inside the binomial tourist-host has an asymmetric character, since each one has actings and different objectives. An exchange of information happens, knowledge, cultures, traditions, among other things that they are derived of the conversations and you chat that they have the tourists and the hosts in those that the communication process happens and it is the space for the cultural promotion of the destination.
Keywords: Relación Turista Anfitrión; Hostales; Arrendamiento; Turismo; Tourism